(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2018)
The study attempts to explore the factors behind selecting Nijhum Dwip for migration and perceive the relative importance of livelihood capitals (Human, physical, natural, financial and social) for the climate change adaptation of migrant community. Both qualitative and quantitative approaches are followed in this study. Data are collected from primary and secondary sources. The study recognizes, people are moving to Nijhum Dwip rather shifting to main land despite facing numerous disasters like cyclone, river bank erosion, flood, storm surge, sea level rise, salinity intrusion and so on. This is mainly due to low price of land and no alternative place to shift. They consider physical capital as the strongest livelihood capital to adapt in this island followed by human capital, natural capital, financial capital as well as social capital are also suitable option for enhancing the adaptation of migrant community to settle there. Asiat. Soc. Bangladesh, Sci. 44(2): 127-136, December 2018